Peningkatan kemampuan psikomotorik siswa dalam pembelajaran bola voli passing atas menggunakan teknik bola pantul pada siswa kelas X MAN 1 Kota Semarang - Angga Pratama; Utvi Hinda Zhannisa; Ibnu Fatkhu Royana (Journal of Physical Activity and Sports (JPAS), 2021)
Angga Pratama, "Increasing the Psychomotor abilities of Students in Learning Top Passing Volleyball Using the Bounce Ball Technique in Class X Students of MAN 1 Semarang City". Essay. Department of Physical Education for Health and Recreation, Faculty of Social Sciences and Sport Education, PGRI University Semarang, 2020. Utvi Hinda Zhannisa, S.Pd., M.Ordan Ibnu Fatkhu Royana, S.Pd., M.Pd. Education is a very important field, especially in Indonesia. In the language of the definition of education is the process of changing the attitudes and behaviour of a person or group of people in an effort to mature humans through teaching and training efforts that are in accordance with the educational procedure itself. The purpose of this study was to determine the improvement of students' psychomotor abilities in learning volleyball using the bounce ball technique in class X students in MAN 1 Semarang City. The design used in this study belongs to the type of quantitative research. The use of a quantitative approach with pre-experimental methods. The population in this study were students of class X in MAN 1 Semarang City. The research sample was taken by means of random sampling. This research will involve 106 students of MAN 1 Semarang City. Based on the calculation, the sig value for pretest data obtained the sig value = 0.064> 0.05. For the posttest data, the sig = 0.056> 0.05 was obtained, so it can be concluded that the pretest and posttest data are homogeneous. The increase in the ability to pretest all volley passing is a minimum of 82,675%. for a maximum value of 89.33%. Data analysis and discussion obtained the following conclusions: There are differences in the psychomotor abilities of students in learning volleyball passing over before and after being given training using the bouncing ball technique in class X MAN 1 Semarang City. From these results, it can be concluded that there is an increase in the psychomotor abilities of students in learning volleyball passing overusing the bouncing ball technique in class X MAN 1 Semarang City students. The increase in the percentage of overpassing ability is 22.38%. It is better if the class X student coaches of MAN 1 Semarang City apply exercises using the bouncing ball technique considering that this exercise has been proven effective in improving students' psychomotor skills in learning volleyball passing over.